2000
DOI: 10.1095/biolreprod63.5.1437
|View full text |Cite
|
Sign up to set email alerts
|

Zona Reaction in Porcine Oocytes Fertilized In Vivo and In Vitro as Seen with Scanning Electron Microscopy1

Abstract: Morphological changes in zona pellucidae (ZP) isolated from in vitro-matured (IVM) and ovulated porcine oocytes were compared before or after fertilization in vitro and in vivo, respectively, by using scanning electron microscopy (SEM). The ZP of some ovulated or IVM oocytes and in vivo- or in vitro-fertilized (IVF) zygotes were equally split into two halves while immersed in an enzyme-inhibitor solution, using a surgical blade. After washing, intact and ZP halves were fixed in 1% glutaraldehyde solution in 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…As the ZP membrane is much softer than the AFM probe, the indenter was modelled as a rigid blunt cone with a tip radius of 10 nm and an angle of aperture of 408. The ZP membrane was instead modelled as an incompressible visco-hyperelastic slab, 30 mm long rsfs.royalsocietypublishing.org Interface Focus 4: 20130066 and 6 mm thick (the value of thickness is consistent with data reported in [22] for porcine oocytes). The FE model simulating the AFM nanoindentation process is shown in figure 1.…”
mentioning
confidence: 93%
“…As the ZP membrane is much softer than the AFM probe, the indenter was modelled as a rigid blunt cone with a tip radius of 10 nm and an angle of aperture of 408. The ZP membrane was instead modelled as an incompressible visco-hyperelastic slab, 30 mm long rsfs.royalsocietypublishing.org Interface Focus 4: 20130066 and 6 mm thick (the value of thickness is consistent with data reported in [22] for porcine oocytes). The FE model simulating the AFM nanoindentation process is shown in figure 1.…”
mentioning
confidence: 93%
“…Although treatments affecting sperm function, such as pretreatment with adenosine before transient exposure to caffeine, reduced polyspermic penetration rate and the width of the window for sperm penetration, the incidence was still unacceptable for commercial application. Ultrastructural observations of the zona pellucida of porcine oocytes (Funahashi et al 2000a) have found morphological differences in the zona pellucida of oocytes matured in vitro and in vivo and these authors hypothesized that the differences due to a failure in final maturation may result in incomplete or delayed zona reaction. Polyspermy rate appears to be affected by the donor of oocytes (Marchal et al 2001) and is still higher for in vitro matured oocytes than for ovulated oocytes (Wang et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A volume of 30 mL of protein-free embryo recovery medium, consisting of Tyrode's lactate (TL)-HEPES-polyvinyl alcohol (PVA) (TL-PVA; [11]) with small modifications [4], was introduced into the uterine horn from the tip of the uterine horn using a 60 mL syringe connected to a blunt needle. The flushing medium was forced through the glass cannula into a 50 mL sterile tube by manual massage of the uterus.…”
Section: Surgical Interventionsmentioning
confidence: 99%